Banking Laws In Malaysia: The Path To The Future - Maruthavanar, Kalavathy (Journal of Malaysian and Comparative Law, 2000)
The banking system in Malaysia consists of two tiers. The first tier is the Central Ban of Malaysia, which is locally known as "Bank Negara Malaysia". BNM is set up pursuant to the Central Bank of Malaysia Act 1958. The role of BNM is set out in section 4 of the aforesaid Act. BNM is basically a bank to the Government and acts as a watchdog over commercial banks and financial institutions.